Attitude and knowledge on oil palm farm biodiversity and willingness to participate in sustainable palm oil certification among oil palm smallholder in Kuala Selangor, Selangor - Ngu, Freddy (2016)
There has been tremendous area expansion for palm oil cultivation throughout the world due to global demand of palm oil-based products especially in Malaysia. The smallholder plays an important role to the global palm oil supply chain. It is expected that global demand for certified sustainable palm oil will increase and participation of independent smallholders in the certified sustainable palm oil supply chain is important. However, participation in sustainable palm oil certification is still lacking especially among Malaysian independent oil palm smallholder. This study was therefore designed to assess smallholders‘ attitude and knowledge on farmland biodiversity and to examine smallholders‘ willingness to participate in palm oil certification scheme. Semi structured interview was used to obtain relevant information from independent smallholders at Kuala Selangor, Selangor. Data collected were analysed using qualitative and quantitative analyses. The study found that smallholders‘ knowledge on oil palm farm biodiversity were narrowed toward pest animal such wild boar and monkey. Almost half of the smallholders have negative feeling toward wild animals on their farm. Nonetheless, smallholders showed considered willingness to join the sustainable palm oil certification with expectation of lower costs of joining the schemes. This study can be used by policy maker or oil palm standard schemes as a reference to develop extension program and promote certification scheme.